KAMPANYE “TASIK BERKISAH” - Evi Novianti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2019)
Tasik Dare to Reduce waste is a message delivered in increasing community action to reduce the level of waste in Tasikmalaya City. Through this campaign, it can convey a message and also at the same time introduce that Nurhayati cares and contributes in realizing the vision of the Tasik Kota Resik. Typical activities in this campaign are publications and documentation. The target public of this campaign is the people of the City of Tasikmalaya, especially the millennial. The model used in this study is The PII Model. In terms of time, this campaign only runs for about two months. Because this campaign is one of the DPR RI's campaign programs, so its focus is divided with other programs. Besides the preparation of the organizers, the authors also considered not professional enough because the committee was filled by individuals who were still learning and had not much experience. The firmer and clearer lines of coordination must build a more professional work culture.